(untitled) (Biosaintifika: Journal of Biology & Biology Education, 2026)
Subterranean termites, particularly Coptotermes curvignathus, are destructive pests that cause serious damage to wood, crops, plantation commodities, and building structures. The development of plant-based semiochemicals may provide an environmentally friendly alternative for termite management by utilizing natural compounds that influence termite orientation behavior. This study aimed to evaluate the olfactory and trail-following responses of C. curvignathus workers to selected plant leaf extracts and to identify their potential roles as attractants, repellents, or trail-disrupting agents. Leaves of cajuput, eucalyptus, citronella, pine, and tea tree were extracted using 70% ethanol, concentrated by rotary evaporation, and analyzed using gas chromatography-mass spectrometry (GC-MS). Olfactory responses were tested using a Y-tube olfactometer, while trail-following behavior was evaluated using a Y-shaped filter paper assay. Each treatment was replicated 15 times using different worker termites, and the data were analyzed using the chi-square test. The highest olfactory response was observed in cajuput extract (80.00%), followed by eucalyptus (60.00%), pine (53.33%), tea tree (40.00%), and citronella (33.33%). In the trail-following assay, cajuput produced the highest positive response (93.33%), followed by pine (80.00%), eucalyptus (53.33%), tea tree (33.33%), and citronella (26.66%). GC-MS analysis showed that cajuput was dominated by α-pinene and 1,8-cineole, while citronella contained geraniol and citronellol, compounds associated with repellent activity. These findings indicate that plant-derived volatile monoterpenes influence termite orientation and trail-following behavior. This research supports SDG 12 and SDG 15 by promoting plant-based termite management and reducing reliance on synthetic termiticides.